Exchange Rate Regimes in the Modern Era: Fixed, Floating, and Flaky - Rose, Andrew K (Journal of Economic Literature, 2011)
This paper provides a selective survey of the incidence, causes, and consequences of a country's choice of its exchange rate regime. I begin with a critical review of Michael Klein and Jay C. Shambaugh's (2010) book Exchange Rate Regimes in the Modern Era, and then proceed to provide an alternative overview of what the economics profession knows and needs to know about exchange rate regimes. While a fixed exchange rate with capital mobility is a well-defined monetary regime, floating is not; thus, it is unclear whether it is theoretically sensible to compare countries across exchange rate regimes. This comparison is quite difficult to make empirically. It is often hard to figure out what the exchange rate regime of a country is in practice, since there are multiple conflicting regime classifications. More importantly, similar countries choose radically different exchange rate regimes without substantive consequences for macroeconomic outcomes like output growth and inflation. That is, the profession knows surprisingly little about either the causes or consequences of national choices of exchange rate regimes. But since the consequences of these choices are small, understanding their causes is of only academic interest. (JEL E52, F33)